Dosage des Inhibiteurs de la calcineurine en Transplantation rénale - EL MARNISSI, Safaa; ELJAOUDI, Rachid; BOUSLIMAN, Yassir; AIT EL CADI, Mina (Jour Med Resh and Health Sci, 2023)
The monitoring of immunosuppressive treatments is an essential tool in the management of renal transplant patients. Currently, calcineurin inhibitors (cyclosporin and tacrolimus) are used as immunosuppressants in the management of transplant patients. The pharmacokinetics of all these agents are complex and variable. In addition, therapeutic monitoring of these drugs is necessary due to their narrow therapeutic ranges, significant variability in blood concentrations between patients. The different stages of the TDM process (pre-analytical, analytical, clinical) are all important and should not be overlooked. The TDM of IS consists in keeping the exposure of the drug within a range of predefined concentrations (therapeutic targets). This monitoring is often based on the blood assay of the residual concentrations of the drug using different types of techniques available, both immunological and chromatographic, whose specificity and ease of use are highly variable. Immunoassays do not make it possible to distinguish the parent molecule from a large number of its metabolites, as do chromatographic methods which, however, have the disadvantage of being technically more complicated to implement and require a significant financial investment, in particular for the detection by mass spectrometry.